Performance of a broth microdilution assay for routine minimum inhibitory concentration determination of 14 anti-tuberculous drugs against the Mycobacterium tuberculosis complex based on the EUCAST reference protocol - Mansjö, Mikael; Espinosa-Gongora, Carmen; Samanci, Ishak; Groenheit, Ramona; Werngren, Jim (Antimicrobial agents and chemotherapy, 2025)
This comparative study aimed at qualifying a broth microdilution (BMD) assay for phenotypic drug susceptibility testing (pDST) of complex (MTBC) strains for implementation in a routine DST workflow. The assay was developed based on the EUCAST (European Committee on Antimicrobial Susceptibility Testing) reference protocol for determination of the minimum inhibitory concentration (MIC) of 14 anti-tuberculous drugs (isoniazid [INH], rifampicin [RIF], ethambutol [EMB], amikacin [AMI], moxifloxacin [MFX], levofloxacin [LFX], bedaquiline [BDQ], clofazimine [CFZ], delamanid [DLM], pretomanid [PA], para-aminosalicylic acid [PAS], linezolid [LZD], ethionamide [ETH], and cycloserine [CS]). Forty MTBC strains with various drug resistance profiles were tested to determine the agreement between MIC results and genotypic drug susceptibility testing (gDST) results derived from whole-genome sequencing (WGS). The agreement between the BMD and gDST results was solid for the majority of the drugs (average agreement 98%, range 90%-100%), including key drugs such as INH, RIF, MFX, LFX, BDQ, DLM, and PA. Ten discrepancies were identified (corresponding to 1.8% of the total number of MIC determinations) and most (8/10) were characterized by MICs equal or close to the potential critical concentration (pCC) applied in the BMD assay. Importantly, the assay can be adjusted to new drug recommendations and concentrations, tailored to local needs. We conclude that the BMD assay provides reliable results, and its implementation in our MTBC routine workflow will produce valuable data that improve our understanding and management of MTBC drug resistance.